Damages on pumps and systems : the handbook for the operation of centrifugal pumps - Merkle, Thomas (Elsevier, 2014)
Damage on Pumps and Systems. The Handbook for the Operation of Centrifugal Pumps offers a combination of the theoretical basics and practical experience for the operation of circulation pumps in the engineering industry. Centrifugal pumps and systems are extremely vulnerable to damage from a variety of causes, but the resulting breakdown can be prevented by ensuring that these pumps and systems are operated properly. This book provides a total overview of operating centrifugal pumps, including condition monitoring, preventive maintenance, life cycle costs, energy savings and economic aspects. Extra emphasis is given to the potential damage to these pumps and systems, and what can be done to prevent breakdown.